Human colonic intraepithelial lymphocytes suppress in vitro immunoglobulin synthesis by autologous peripheral blood lymphocytes and lamina propria lymphocytes. - Sachdev, G; Dalton, H; Hoang, P; DiPaolo, M; Crotty, B; Jewell, D (1993)
Human colonic intraepithelial lymphocytes have been shown to suppress the proliferation of autologous lamina propria lymphocytes and allogeneic peripheral blood mononuclear cells. This study has shown that, in vitro, intraepithelial lymphocytes suppress IgA and total immunoglobulin synthesis (but not IgG or IgM production) by autologous peripheral blood and lamina propria lymphocytes. This down regulation of IgA production is mediated by a soluble factor secreted by the intraepithelial lymphocytes. There is no difference in immunoglobulin down regulation by intraepithelial lymphocytes of control subjects and patients with inflammatory bowel disease.